PATTERN OF SODIUM THIOPENTAL-INDUCED SLEEP IN WISTAR RATS IN DOSES OF ARTESUNATE AND ETHANOLIC EXTRACT OF GARCINIA KOLA - Ezenwanne, E B; O, Abuda (Pakistan Journal of Physiology, 2016)
Background: There are several reports of the medicinal applications of Garcinia kola and the efficacy of various other uses of this plant. The fact remains that emphasis is rapidly shifting from synthetic drugs to the use of plant materials for medicinal formulations. This study was undertaken to compare the patterns of thiopental-induced sleep in separately administered doses of Garcinia kola extract and artesunate in Wistar rats. Methods: The onset and duration of the induced sleep were computed in 40 mg/Kg dose of thiopental sodium in Wistar rats, after pretreatments in separate doses of Garcinia kola extract and artesunate. Results: Opposing influences or negative effects on the induced sleep was observed in doses of Garcinia kola extract. A clear facilitating influences or promoting effects on the induced sleep was observed in doses of artesunate. Conclusion: It is believed that the dopaminergic neural mechanism may have accounted for the opposing influences of Garcinia kola on the thiopental-induced sleep observed in this study. The present result was also suggestive that the facilitating influences of artesunate on the induced sleep was mediated through GABA neuronal mechanism in the central processes of sleep production. Pak J Physiol 2016;12(4):3–6